Effects of earthquakes on buildings - Herak, Marijan; Herak, Davorka (Geofizika, 2009)
Foreword to the English translation The 1908 Messina (Italy) earthquake triggered intense activity among seismologists and engineers who started to seriously consider seismically resistant construction (see, for instance the paper by Sorentino, 2007). Andrija Mohorovičić was no exception. At the time he was a director of the Meteorological Observatory in Zagreb, but all of his scientific interests were already directed towards seismology (more on his life and work may be found in e.g. Skoko and Mokrovi}, 1982, 1998, or Herak and Herak, 2007). Although he was mostly interested in physical aspects of earthquakes and wave propagation (his greatest scientific accomplishment – proof of the existence of the crust-mantle boundary – is less than two years away), Mohorovičić was always deeply concerned with the engineering aspect of the problem. For instance, in his overview paper on the developments in seismology (Mohorovičić, 1913), he wrote: »… Systematic study of earthquakes has also one very practical aspect. Strong earthquakes often cause great damage to houses and other buildings, and occasionally they level to the ground large and rich cities, and bury thousands of people under the ruins. Therefore, one of the most important goals of seismology is to theoretically study how the movement of the earth affects buildings, and to apply these results as well as the experience gained in catastrophic earthquakes to show the ways of constructing buildings resistant as much as possible against earthquakes. …« This topic was apparently a matter of great importance for him. On March 1, 1909, he held a lecture at the Croatian Society of Engineers and Architects (CSEA), in which he attempted to explain how the earth shakes during earthquakes, and what are the effects of this shaking on buildings. Later that year, in the newspaper article dedicated mostly to the effects of the Kupa valley earthquake of October 8 (the analyses of which led him to his epochal discovery), he describes damage to houses and other buildings, and adds: »… I take this opportunity to warn all responsible institutions of outdated building codes, which completely disregard the ways earthquakes affect buildings. In March of this year I have delivered a lecture on that subject in the Society of Engineers and Architects in Zagreb, and I stressed the need to consider earthquakes when buildings are constructed. I will soon publish the extended edition of the lecture. So far, my appeals fell on deaf ears; after the lecture, many buildings were erected in Zagreb that pose threat for passers-by, as well as to themselves.…« (Mohorovičić, 1909a). Although – as he puts it – his was the voice of a man lost in the desert, there has been some response from authorities. The archives of the Department of Geophysics hold a letter (filed on April 18, 1910) from the Royal Department of Religion and Education in which he is asked to provide advice on how to construct schools, churches and parish houses to better resist earthquakes. Mohorovičić responded the same day, eagerly agreeing to act as consultant. He informed the Department that he has already finished the manuscript describing his studies (based on the above mentioned lecture), and urges the government to persuade the Department of Civil Engineering to cover the cost of publication. The letter ends with: »… The book would be useful not only to the Royal Department of Civil Engineering, but also to the architects and entrepreneurs. It would promote improvement of the construction process, and would certainly stimulate many experts to keep considering this subject, and to use experience to perfect what the undersigned has started.« On May 5, 1910 Mohorovičić despatched a 23-page document addressed to the Division of Internal Affairs and its Department of Civil Engineering, in which he put forward a remarkably detailed plan of actions leading to improvement of the building and construction in order to secure seismic resistance of edifices. As far as we know, the Government did not react at all… The extended version of the lecture of 1909 was eventually published in 1911 in 9 sequels in the News of the CSEA (Mohorovičić, 1911a), and was reprinted in a booklet later in the same year (Mohorovičić, 1911b). This study, regarded by the Croatian scientific community to be the origin of engineering seismology in Croatia, is unknown to non-Croatian speaking professionals. On the centennial of the lecture, the Editorial board of Geofizika decided to publish its translation into English, thus providing the international seismological and civil engineering community an insight into this, generally unrecognized, aspect of Mohorovičić’s professional activity. The study itself is typical of most of the Mohorovičić’s opus – it is a thorough, multifaceted insight into the problem of aseismic building design, with special emphasis to building types most frequently found in Croatia of that time. Being a transcript of articles from a non-scientific publication, only one formal reference – Baratta (1910) – is found of previous work done by foreign researchers. Nevertheless, Mohorovičić refers to unspecified Omori’s papers and other Japanese investigations in several places. That he was in large part inspired by the work of Japanese and British seismologists working in Japan, is also clear from another lecture he gave in the CSEA (Mohorovičić, 1909b) about the Japanese studies on earthquake resistant buildings, citing works by Omori (1901) and Kikuchi (1904). The study has an Introduction where Mohorovičić presents his motivation, but also introduces concepts of seismic hazard and earthquake risk in such a way that 100 years later, there is little one could add or improve. He deals with inhomogeneous distribution of seismicity, distinguishes between buildings according to their purpose and expected life-span, and even gives financial and economical motivation for building earthquake resistant houses. To the best of our knowledge, this is the first time anyone (in Croatia) attempted to use earthquake statistics to estimate cumulative effects a building will have to withstand during its lifetime. Here he also warns against the practice of considering only static loads, completely disregarding external excitation (except, occasionally, the wind). The Introduction is followed by paragraphs in which Mohorovičić presents basic physics of the shaking of the ground during earthquakes. He clearly identifies resonance of the buildings and earthquake waves as the primary threat to structures, and goes on to describe eigen- and forced vibrations of buildings. In the main body of the paper Mohorovičić analyses most common building elements and building types and their resistance and response to earthquake shaking. His excellent physical background helped him to deal not only with the simplest structures (like columns), but also with rather complicated buildings types. The calculations enabled him to draw a number of rules to be observed in order to build earthquake-resistant buildings, which are presented in the concluding paragraph. One century later, the 15 Mohorovičić’s rules are still valid and applicable, which is easy to confirm if one compares them with the basic principles of conceptual design as listed in Eurocode-8 (2004). Marijan Herak Davorka Herak